Literary Criticism in English Periodicals, 1749-1759 - Combs, Laas frances (My University, 1970)
The purpose of this thesis is to examine the place of literary criticism in the periodical literature of the decade 1749-1759 and to set forth the critical principles expressed in these periodicals; with special emphasis on movements in criticism, related to the development of the novel and biography. Although most of the relevant available periodical have boen used to some extent the examination concentrates on four periodicals which are not readily available and have received little scholarly attention, the Ladies Magazine (1749-1753), the General Review (1752), the Literary Magazine (1756-1758), and the Weekly Magazine and Literary Review (1758).
Keywords: English Language and Literature; English Language and Literature